Modulating the Mechanical Activation of TRPV4 at the Cell-Substrate Interface - Sianati, Setareh; Schroeter, Lioba; Richardson, Jessica; Tay, Andy; Lamandé, Shireen R.; Poole, Kate (Frontiers in Bioengineering and Biotechnology, 2021)
Ion channels activated by mechanical inputs are important force sensing molecules in a wide array of mammalian cells and tissues. The transient receptor potential channel, TRPV4, is a polymodal, nonselective cation channel that can be activated by mechanical inputs but only if stimuli are applied directly at the interface between cells and their substrate, making this molecule a context-dependent force sensor. However, it remains unclear how TRPV4 is activated by mechanical inputs at the cell-substrate interface, which cell intrinsic and cell extrinsic parameters might modulate the mechanical activation of the channel and how mechanical activation differs from TRPV4 gating in response to other stimuli. Here we investigated the impact of substrate mechanics and cytoskeletal components on mechanically evoked TRPV4 currents and addressed how point mutations associated with TRPV4 phosphorylation and arthropathy influence mechanical activation of the channel. Our findings reveal distinct regulatory modulation of TRPV4 from the mechanically activated ion channel PIEZO1, suggesting the mechanosensitivity of these two channels is tuned in response to different parameters. Moreover, our data demonstrate that the effect of point mutations in TRPV4 on channel activation are profoundly dependent on the gating stimulus.